ADOPTERs of Innovation in a Crisis: The History of Vera Gedroits, Kanehiro Takaki and the Russo-Japanese War of 1904–1905 - Pratik Raichurkar, BMed; Devesh Kaushal, MBBS, MS, FRACS; Robert Beaumont Wilson, MBBS (Hons 1), BSc, FRACS, FACS (Annals of Surgery Open)
The 1904–1905 Russo-Japanese War was the first “modern” conflict, using rapid-firing artillery and machine guns, fought over imperial ambitions in Korea and Manchuria. During the war, Princess Vera Gedroits pioneered early laparotomy for penetrating abdominal wounds with unprecedented success. Her techniques were then adopted by the Russian Society of Military Doctors. However, Allied forces took 10 years to adopt operative management of penetrating abdominal wounds over conservative management. Gedroits was later appointed in Kyiv as the world’s first female Professor of Surgery. Kanehiro Takaki, a Japanese Naval surgeon, showed in 1884 a diet of barley, meat, milk, bread, and beans, rather than polished white rice, eliminated beriberi in the Japanese Navy. Despite this success, the Japanese Army failed to change the white rice rations until March 1905. During the 1904–1905 Russo-Japanese War, an estimated 250,000 Japanese soldiers developed beriberi, of whom 27,000 died. Japan’s 1905 defeat of Russia sowed the seeds of discontent with Tsar Nicholas’ rule, culminating in the 1917 Russian Revolution. Although the Russian Navy was destroyed, Japan ceded North Sakhalin Island to Russia in peace negotiations, and Russia seized Manchuria, South Sakhalin, and the Kuril Islands in 1945. We highlight the contributions of Gedroits and Takaki, 2 intellectual prodigies who respectively pioneered rapid triage and surgical management of trauma and a cure for beriberi. We aim to show how both these surgeons challenged entrenched dogma and the cultural and political zeitgeist, and risked their professional reputations and their lives in being ADOPTERs of innovation during a crisis.